Solve the system by the elimination method. 2x + y - 4 = 0 2x - y - 4 = 0 When you eliminate y, what is the resulting equation? x = 0 4x = -8 4x = 8

Respuesta :

4x=8
This is because when you add the two expression together 2x+2x=4x the y values cancel and -4+-4=-8
4x-8=0 is equivalent to 4x=8

Answer:

Option C.

Step-by-step explanation:

System of the equation consists of two equations

2x + y - 4 = 0

2x + y - 4 + 4 = 0 + 4

2x + y = 4--------(1)

and 2x - y - 4 = 0

2x - y + 4 - 4 = 0 + 4

2x - y = 4------(2)

Now we will add these equations to eliminate y.

(2x + y) + (2x - y) = (4 + 4)

(2x + 2x) + (y - y) = 8

4x = 8

Therefore, resulting equation will be 4x = 8

Option C. will be the answer.